The Outcomes of Open Ankle Fractures in Patients Managed by Early or Delayed Definitive Fixation: A Comparative Analysis of 73 Patients - Kaganur, Raghavendra; Sarkar, Bhaskar; Jaisankar, Pragadeeshwaran; Paul, Nirvin; Azam, Md Quamar; Bhakhar, Anurag (Journal of Korean Foot and Ankle Society, 2024)
Purpose: Ankle fracture fixation is the gold standard of treatment but it does have its own complications. There is inadequate data re- garding the comparative effectiveness of early vs. delayed fixation for open ankle fracture outcomes. This study compares the clinical and functional outcomes of open ankle fractures treated by early or delayed definitive fixation and identifies the limitations of both methods. Materials and Methods: All 73 patients enrolled in the study underwent surgical intervention within 24 hours of injury. The early fixa- tion group (group A) consisting of 39 patients underwent definitive fixation as an index procedure, while the delayed fixation group (group B) consisted of 34 patients who underwent debridement and external fixator application as an index procedure and defini- tive fixation when soft tissue condition was conducive. All patients were evaluated at 2, 6, and 12 weeks postoperatively and then three monthly for a year. Results: Enneking and American Orthopaedic Foot and Ankle Society scores were markedly higher in the early fixation group at 6 months postoperatively (p-values <0.001 and 0.011, respectively). However, no discernible intergroup difference was evident at 12 months postoperatively. Between 6 and 12 months, group functional outcome scores were significantly different. At 6 months, there was a substantial difference in dorsiflexion between the two groups (p-values 0.001 and <0.001, respectively), but no difference was observed at 12 months postoperatively. At 6 and 12 months, group average plantar flexions were non-significantly different. Conclusion: Early definitive fixation of complex ankle fractures using a targeted approach produced promising results for lower grade open fractures (grades 1 and 2), and delayed definitive fixation, after initial external fixation to allow for soft tissue stabilization, pro- duced promising results for higher grade open fractures (grades 3A and 3B). At 12-month follow-ups, clinical and functional outcomes achieved using these strategies were equivalent. KCI Citation Count: 0